Pola Rekrutmen Sumber Daya Manusia di Pondok Pesantren (Studi Komparatif Pesantren Syaikh Zainuddin NW Anjani dan Maraqitta'limat Mamben) - Hidayatullah, Syarif; Hakim, Lukman; Ahyar, Ahyar (MODELING: Jurnal Program Studi PGMI, 2024)
This study aims to: (1) Describe the analysis of human resource needs in two Islamic boarding schools (Comparative Study of Pesantren Syaikh Zainuddin NW Anjani and Maraqitta'limat Mamben). (2) Describe the implementation of human resource recruitment within the religious education environment at the Islamic boarding schools (Comparative Study of Pesantren Syaikh Zainuddin NW Anjani and Maraqitta'limat Mamben). (3) Describe the placement of human resources in the two Islamic boarding schools (Comparative Study of Pesantren Syaikh Zainuddin NW Anjani and Maraqitta'limat Mamben). This study uses a qualitative method. The research locations are at MAK Hamzanwadi II and MA Maraqitta'limat Mamben. The data collection process involves observation, in-depth interviews, and documentation (triangulation). Data analysis is conducted using the Milles, Huberman, and Saldana techniques, which include data collection, data reduction, data presentation, and conclusion drawing. To ensure data validity, testing is conducted through the criteria of credibility, transferability, dependability, and confirmability.This study analyzes the recruitment of educators at Pondok Pesantren Syaikh Zainuddin NW Anjani and Pondok Pesantren Maraqitta'limat Mamben. The process involves needs analysis, setting requirements, information dissemination, and candidate selection. Recruitment is based on religious values and competence, encompassing application submission, interviews, and document selection. The placement of educators is carefully arranged to ensure maximum contribution, with an emphasis on integrity, loyalty, and educational mission.